Agar-agar from seaweeds a plant design - Ang, Alfonso C. (College of Engineering, 1976)
Capacity: 100,000 kgs/year -- Land area: 4 hectares -- Sea area (concession area): 25 hectares -- Total capital investment: P 7,945,853.2 -- Total product cost at max. production: P 1,735,376 -- Annual sales at max. production: P 4,800,000 -- Payout period: 4.31 years -- Break-even point: 20% of maximum operating capacity